Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Sure! Let's solve the system of linear equations step-by-step. The given equations are:
1) [tex]\( y = 2x - 1 \)[/tex]
2) [tex]\( y = 5 - x \)[/tex]
To find the solution, we need to determine the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] where both equations intersect.
### Step-by-Step Solution:
1. Setting the equations equal to each other:
Since both equations equal [tex]\(y\)[/tex], we can set them equal to each other:
[tex]\[ 2x - 1 = 5 - x \][/tex]
2. Solving for [tex]\(x\)[/tex]:
Combine like terms to solve for [tex]\(x\)[/tex]. Add [tex]\(x\)[/tex] to both sides:
[tex]\[ 2x + x - 1 = 5 \][/tex]
Simplify:
[tex]\[ 3x - 1 = 5 \][/tex]
Add 1 to both sides:
[tex]\[ 3x = 6 \][/tex]
Finally, divide by 3:
[tex]\[ x = 2 \][/tex]
3. Finding [tex]\(y\)[/tex] using one of the original equations:
Substitute [tex]\(x = 2\)[/tex] into either of the two original equations. Let's use [tex]\(y = 2x - 1\)[/tex]:
[tex]\[ y = 2(2) - 1 = 4 - 1 = 3 \][/tex]
### Solution:
The solution for the system of equations is:
[tex]\[ (x, y) = (2, 3) \][/tex]
This means the two lines intersect at the point [tex]\((2, 3)\)[/tex].
### Graphing the equation [tex]\(y = 2x - 1\)[/tex]:
1. Locate the y-intercept:
The y-intercept is where [tex]\(x = 0\)[/tex]. For the equation [tex]\(y = 2x - 1\)[/tex]:
[tex]\[ y = 2(0) - 1 = -1 \][/tex]
So the y-intercept is (0, -1).
2. Use the slope:
The slope of the equation [tex]\(y = 2x - 1\)[/tex] is 2. This means for every increase of 1 in [tex]\(x\)[/tex], [tex]\(y\)[/tex] increases by 2.
3. Plotting another point using the slope:
Starting from the y-intercept (0, -1), move 1 unit to the right (increase [tex]\(x\)[/tex] by 1) and 2 units up (increase [tex]\(y\)[/tex] by 2). This gives the point (1, 1).
4. Draw the line:
Connect the y-intercept (0, -1) and the point (1, 1), and extend the line in both directions.
By graphing both equations, you would visually find that they intersect at the point (2, 3). This confirms our algebraic solution.
1) [tex]\( y = 2x - 1 \)[/tex]
2) [tex]\( y = 5 - x \)[/tex]
To find the solution, we need to determine the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] where both equations intersect.
### Step-by-Step Solution:
1. Setting the equations equal to each other:
Since both equations equal [tex]\(y\)[/tex], we can set them equal to each other:
[tex]\[ 2x - 1 = 5 - x \][/tex]
2. Solving for [tex]\(x\)[/tex]:
Combine like terms to solve for [tex]\(x\)[/tex]. Add [tex]\(x\)[/tex] to both sides:
[tex]\[ 2x + x - 1 = 5 \][/tex]
Simplify:
[tex]\[ 3x - 1 = 5 \][/tex]
Add 1 to both sides:
[tex]\[ 3x = 6 \][/tex]
Finally, divide by 3:
[tex]\[ x = 2 \][/tex]
3. Finding [tex]\(y\)[/tex] using one of the original equations:
Substitute [tex]\(x = 2\)[/tex] into either of the two original equations. Let's use [tex]\(y = 2x - 1\)[/tex]:
[tex]\[ y = 2(2) - 1 = 4 - 1 = 3 \][/tex]
### Solution:
The solution for the system of equations is:
[tex]\[ (x, y) = (2, 3) \][/tex]
This means the two lines intersect at the point [tex]\((2, 3)\)[/tex].
### Graphing the equation [tex]\(y = 2x - 1\)[/tex]:
1. Locate the y-intercept:
The y-intercept is where [tex]\(x = 0\)[/tex]. For the equation [tex]\(y = 2x - 1\)[/tex]:
[tex]\[ y = 2(0) - 1 = -1 \][/tex]
So the y-intercept is (0, -1).
2. Use the slope:
The slope of the equation [tex]\(y = 2x - 1\)[/tex] is 2. This means for every increase of 1 in [tex]\(x\)[/tex], [tex]\(y\)[/tex] increases by 2.
3. Plotting another point using the slope:
Starting from the y-intercept (0, -1), move 1 unit to the right (increase [tex]\(x\)[/tex] by 1) and 2 units up (increase [tex]\(y\)[/tex] by 2). This gives the point (1, 1).
4. Draw the line:
Connect the y-intercept (0, -1) and the point (1, 1), and extend the line in both directions.
By graphing both equations, you would visually find that they intersect at the point (2, 3). This confirms our algebraic solution.
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.